3(8-2x)=6(3x-2)

Simple and best practice solution for 3(8-2x)=6(3x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8-2x)=6(3x-2) equation:



3(8-2x)=6(3x-2)
We move all terms to the left:
3(8-2x)-(6(3x-2))=0
We add all the numbers together, and all the variables
3(-2x+8)-(6(3x-2))=0
We multiply parentheses
-6x-(6(3x-2))+24=0
We calculate terms in parentheses: -(6(3x-2)), so:
6(3x-2)
We multiply parentheses
18x-12
Back to the equation:
-(18x-12)
We get rid of parentheses
-6x-18x+12+24=0
We add all the numbers together, and all the variables
-24x+36=0
We move all terms containing x to the left, all other terms to the right
-24x=-36
x=-36/-24
x=1+1/2

See similar equations:

| (2y+3)3y=8 | | 9-(2+3x)=x-17 | | (7x+7)=(5x+24) | | 18=3(3x−6) | | 6(-1+5x)=-266 | | 3(j-68)=54 | | D=3x-15x | | 11=-3(2y-2)-7 | | 41x-4x=13-8x | | 41x−4x=13−8x | | 10-2x=-6+6x | | 4x+11=-59−6x | | 0.4x-7=0.3x=2.8 | | 3x*4x=34 | | 5x2+16x-15=0 | | 2/3a+2=4/3+1/3 | | -6/7w=-36 | | x+21,7=40,4 | | -151=-10c+9 | | -s=71 | | z+22,7=38,4 | | 144-108+2x=180 | | 7(x-7)=-28x= | | y/13-2=6 | | 20x+3x-19x-3x+x=14 | | 50,000=2/3x+12 | | 68=12+8x | | w+4.5=8.11 | | 5(2x+25)=225 | | 4u-u+3u+3u-3u=18 | | 31=5x+9 | | 13=c/3-10 |

Equations solver categories